Aqueous microwave-assisted cross-coupling reactions applied to unprotected nucleosides - Hervé, Gwénaëlle; Len, Christophe (Frontiers in Chemistry, 2015)
Metal catalyzed cross-coupling reactions have been the preferred tools to access to modified nucleosides (on the C5-position of pyrimidines and on the C7- or C8-positions of purines). Our objective is to focus this mini-review on the Suzuki-Miyaura and on the Heck cross-couplings of nucleosides using microwave irradiations which is an alternative technology compatible with green chemistry and sustainable development